Design feasibility test instrument for sports tourism domain contextual events based on local wisdom - Tri Setyo Guntoro; Yudik Prasetyo; Miftah Fariz Prima Putra; Fitri Agung Nanda; Titis Pambudi; Dewi Nurhidayah (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Instruments are very important to develop for assessing a sports tourism design.